Edukacja i wychowanie czy indoktrynacja i propaganda? Ideowe oblicza oświaty w placówkach Związku Patriotów Polskich na przykładzie Południowego Kazachstanu (1944–1946) - Marciniak, Wojciech (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2025)
After 1943, the organisation of education for Polish children in the USSR included the incorporation of communist ideology and Stalinist propaganda into the curriculum. The Polish Patriots’ Union in the USSR, which promoted the slogans of “Polish-Soviet friendship” and the post-war alliance between Poland and its eastern neighbour, was responsible for re-establishing and expanding the network of educational institutions. The practice of operating schools, kindergartens, orphanages and boarding schools under the banner of the PPU showed varying degrees of compulsory propaganda. Examining this issue on the example of South Kazakhstan (i.e., the South Kazakhstan Oblast) reveals the scale of indoctrination. It allows for an assessment of whether, in practice, more effort was made to impart knowledge or whether education served merely as a pretext for political and educational work.
p. 119-154
Summary in English and Russian.
Keywords: Union of Polish Patriots in the USSR; Polish education in the USSR; orphanages in the USSR; deportees; Kazakhstan; deportations; indoctrination; propaganda; World War, 1939-1945 - deportations from Poland; Polish children - education - Soviet Union - 1900-1945; World War, 1939-1945 - children